2007
DOI: 10.1021/ie060781y
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexanol Production via Esterification of Cyclohexene with Formic Acid and Subsequent Hydration of the EsterReaction Kinetics

Abstract: An alternative to current production routes to cyclohexanol, the esterification of cyclohexene with formic acid and subsequent splitting of the ester can overcome many of the drawbacks associated with conventional processes. The process that is being considered could be carried out in a reactive distillation column. To develop such a process, reliable data on liquid−liquid and vapor−liquid phase-splitting behavior and on reaction kinetics is of high importance. The current publication focuses on the reaction k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 15 publications
(11 reference statements)
0
51
0
Order By: Relevance
“…In addition, although direct hydration is highly selective, increasing economic benets to a certain extent and reducing the possibility of danger in the two traditional production processes, it allows only a very low conversion per pass, because of slightly exothermic and equilibrium limited. 5 To overcome the main problem of the thermodynamic equilibrium limitation of the direct hydration reaction of cyclohexene, the indirect hydration of cyclohexene was born out, which is a two-step process using formic acid as a reactive entrainer. [6][7][8][9] In the rst step, cyclohexene react with formic acid to produce cyclohexylformate, which is an electrophilic addition esterication, 10 needing acid catalyst to increase the conversion rate of cyclohexene.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, although direct hydration is highly selective, increasing economic benets to a certain extent and reducing the possibility of danger in the two traditional production processes, it allows only a very low conversion per pass, because of slightly exothermic and equilibrium limited. 5 To overcome the main problem of the thermodynamic equilibrium limitation of the direct hydration reaction of cyclohexene, the indirect hydration of cyclohexene was born out, which is a two-step process using formic acid as a reactive entrainer. [6][7][8][9] In the rst step, cyclohexene react with formic acid to produce cyclohexylformate, which is an electrophilic addition esterication, 10 needing acid catalyst to increase the conversion rate of cyclohexene.…”
Section: Introductionmentioning
confidence: 99%
“…In the second step, the ester readily hydrolyzes to produce cyclohexanol. Steyer et al 5,6,11 simulates the indirect hydration process using two distillation towers. Sulfonic-acid resin Amberlyst-15 catalyzed the esterication of cyclohexene with formic acid in the rst distillation tower, the hydrolysis of cyclohexyl formate occurred in the second column.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the energy requirement is very high. 17,18 Hence, Freund and co-workers concluded that unless a right catalyst can be developed, this process is economically not viable. 19 Herein, we report a novel cyclohexene esterification-hydrogenation process for the production of cyclohexanol (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…By using acid and salt catalyst there was formation of side reactions and also reaction required higher temperature. Reference [4] studied production of cyclohexanol, the esterification of cyclohexene with formic acid. Reactive distillation column was used for this purpose.…”
Section: Introductionmentioning
confidence: 99%